"Fake" Journals and the Fragility of Authenticity: Citation Indexes, "Predatory" Publishing, and the African Research Ecosystem. Issue 3 (3rd July 2021) - Mills, David; Branford, Abigail; Inouye, Kelsey; Robinson, Natasha; Kingori, Patricia
ABSTRACT: This article explores the contested politics of academic authenticity within the African research ecosystem, with particular reference to Nigeria. We show how a fear of "fake" journals is cultivated amongst African academics, with international journal citation indexes being used to adjudicate the credibility of African journals and publishers. The article juxtaposes an ethnographic vignette of a major publisher's training webinar with detailed case studies of two Nigerian commercial publishing houses. Established by entrepreneurial academics in response to limited local journal capacity and the exclusions enacted by Northern editorial gatekeeping, their journals have low article processing charges and, in some cases, minimal peer-review. One publisher was labelled as "predatory" in Beall's list, leading to its journals being removed from Scopus, the Elsevier-owned journal citation index. The other has struggled to get its journals listed in alternative journal databases, such as the Directory of Open Access Journals. The article explores how these citation indexes become contested markers of academic authenticity. We end by reflecting on the implications of this index-linked credibility for the future of African journals and the circulation of research knowledge across the continent.